2006
DOI: 10.1111/j.1440-1819.2006.01457.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychological impact of verbal abuse and violence by patients on nurses working in psychiatric departments

Abstract: The aim of this study was to assess the psychological impact of verbal abuse or violence by patients on nurses working in psychiatry departments and to identify factors related to their impact. Survey sheets were distributed to a total of 266 nurses working at two hospitals, and replies were obtained from 232 of them. Because three of them had less than 1 month of experience working in the psychiatry department and four of them failed to answer all the questions, valid replies were obtained from 225 nurses. Am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
85
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 22 publications
3
85
0
5
Order By: Relevance
“…Findings of two studies conducted in a mental health hospital in our country showed that healthcare professionals and especially nurses are drastically exposed to violence (3,7). It is observed that findings of studies in other countries (6,13,14) are in consistency with ours; and besides this, it has been detected in some studies that in-ward violence events were not reported (15,16).…”
Section: Introductionsupporting
confidence: 80%
See 1 more Smart Citation
“…Findings of two studies conducted in a mental health hospital in our country showed that healthcare professionals and especially nurses are drastically exposed to violence (3,7). It is observed that findings of studies in other countries (6,13,14) are in consistency with ours; and besides this, it has been detected in some studies that in-ward violence events were not reported (15,16).…”
Section: Introductionsupporting
confidence: 80%
“…The study by Gokce and Dundar (3) that had been conducted in the mental health hospital in Samsun demonstrated the progressively increasing anxiety associated with exposure to violence. The study carried out by Inoue et al (13) on nurses who were exposed to violence showed that violence influenced the nurses adversely whereas the family support contributed to their psychological state. Kindy et al (22) displayed that the nurses, who were applied violence, failed to feel the workplace conditions safe but feel depressed, highly excitable, and unsafe and have been afraid of interacting with patients.…”
Section: Discussionmentioning
confidence: 99%
“…Hasil ini didukung oleh beberapa studi. Perawat adalah profesi yang paling rentan menjadi target kekerasan (Holmes, et al, 2004;Inoue, et al, 2006), sebagian besar perawat mengalami kekerasan selama karir mereka (Inoue, et al, 2006;Landy, 2005).…”
Section: Pembahasanunclassified
“…The demographic variables under consideration include one continuous variable (age), two dichotomous variables (gender and full time employment), and several categorical variables (income, marital status, education, occupational groupings, and place of employment). Each of the independent variables is expected to have an effect on job satisfaction and workplace stress which in turn have an effect on lifestyle choices and productivity: demographic characteristics such as age, marital status and education [18][19][20], working situations such as job rank, work time [13,[21][22][23]. In this sample the individuals are categorized into three groups based on their marital status: divorced, legally separated or widowed, legally married or in a common law relationship, and single.…”
Section: The Independent Variablesmentioning
confidence: 99%